Biomimetic catalysts of iron-based metal–organic frameworks with high peroxidase-mimicking activity for colorimetric biosensing. Issue 11 (3rd March 2021) - Wang, Xiao-Ning; Zhao, Yumeng; Li, Jia-Luo; Pang, Jian-Dong; Wang, Qiang; Li, Bao; Zhou, Hong-Cai
Abstract : Two MOFs exhibit distinct secondary building units (SBUs) and topological structures, which could be used as biomimetic catalysts for the systematic comparisons of structural characteristics and the catalytic activity. Abstract : The field of metal–organic framework (MOF)-based biomimetic catalysts has achieved great progress but is still in its infancy. The systematic investigation of the tailored construction of MOF-based biomimetic catalysts is required for further development. Herein, two iron-based MOFs, namely, [(Fe3 O)2 (H2 O)4 (HCOO)(L)2 ] n (HUST-5: H6 L = hexakis(4-formylphenoxy) cyclotriphosphazene; HUST = Huazhong University of Science and Technology) and [(Fe3 O)(H2 O)3 (L)] n (HUST-7) have been fabricated through the assembly of different iron clusters and hexa-carboxylate ligand under the control of the added acid species. The two MOFs exhibit distinct secondary building units (SBUs) and topological structures, which could be used as biomimetic catalysts for the systematic comparisons of structural characteristics and the catalytic activity. Both MOFs possess catalytic activity similar to that of natural peroxidases towards the catalysis of the oxidation of a variety of substrates. Significantly, HUST-5 and HUST-7 can effectively catalyze the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) by H2 O2 accompanied by significant colorimetric biosensing. With same compositions, different catalytic performances were obtained due to differences in the porous structures and characteristics of SBUs in two Fe-MOFs, which was also validated by theoretical calculation results. Furthermore, the phenomenon of colorimetric biosensing could be significantly suppressed by the addition of ascorbic acid (AA) during the oxidation process of TMB. It was observed from these findings that a facile colorimetric biosensing platform for detecting H2 O2 and ascorbic acid has been successfully explored. Therefore, this work provides another unique perspective for the tailor-made preparation of stable MOF-based peroxidase mimics with excellent catalytic performance and colorimetric biosensing.